Pembuatan Sirup Kelapa Untuk Usaha Rumah Tangga di Lamdingin Kecamatan Kuta Alam Kota Banda Aceh - Rahmah, Ade Elvi; Fuady, Vaudhan; Afifudin, Said; Hamdi, Iswar (PT. Alahyan Publisher Sukabumi, 2025)
Coconut (Cocos nucifera) is an important plantation commodity in Indonesia, with production centers spread across various regions, including Aceh. The abundant potential of coconut fruit provides a great opportunity to develop processing businesses, including the utilization of by-products such as coconut water. Coconut water is rich in nutrients and can be processed into value-added products such as coconut syrup. The village of Lamdingin in Banda Aceh City has the potential for micro, small, and medium enterprises (MSMEs), but the abundant coconut water in the local market is often wasted. The community service activity aims to provide training in coconut syrup production for housewives in Gampong Lamdingin. This community service activity was conducted on Wednesday, July 31, 2024, in Gampong Lamdingin, Kuta Alam District, Banda Aceh City. This training provides knowledge to the community to enhance household economic income, family food security, and develop local potential through the utilization of coconut by-products.